A COMBINATION OF PIGMENTED VILLONODULAR SYNOVITIS AND SYNOVIAL CHONDROMATOSIS PRESENTING AS A LARGE LOOSE BODY IN KNEE - Shetty, Siddharth; Shetty, Vikram; Shetty, B. J.P.; Bhat, Shubha P. (Journal of Health and Allied Sciences NU, 2012)
Intra-articular calcific lesions of knee usually manifest as loose bodies with symptoms of recurring episodes of locking and restriction of movement. These loose bodies are a consequence of trauma or degeneration of structures in the joint and occasionally may be of inflammatory or neoplastic condition of the synovium.Here we present our case as a rare form of presentation where in our patient had a large loose body in the knee with chronic pain and swelling and restriction of the movements of knee. Arthrotomy, loose body excision and total synovectomy of the knee confirmed coexistence of a dual lesion of synovial chondromatosis of the Hoffa's fat pad with diffuse pigmented villonodular synovitis of the knee joint. The patient made an uneventful recovery and full range of knee movement was restored by end 3 months. These benign conditions have inherent risk of recurrence, and in our case, till the last follow up at 14 months after surgery, he has remained asymptomatic with no clinico radiological evidence of any recurrence.
Keywords: Synovial chondromatosis; pigmented villonodular synovitis; loose body in knee; Hoffa's fat pad